The Propagation Properties of a Longitudinal Orbital Angular Momentum Multiplexing System in Atmospheric Turbulence - Qinghua Tian; Lei Zhu; Yongjun Wang; Qi Zhang; Bo Liu; Xiangjun Xin (IEEE Photonics Journal, 2018)
A novel multichannel free-space optical (FSO) communication system based on orbital angular momentum (OAM) carried by frozen waves with different longitudinal patterns is studied in this paper. The longitudinal OAM multiplexing (LOAMM) system is simulated under atmospheric turbulence, which is based on the split-step Fourier transform method and includes multiple random phase screens. The influences of system parameters on the average OAM mode probability densities are analyzed and discussed, such as propagation distance, strength of turbulence, sizes of finite aperture function, OAM mode numbers, and source parameters. It is found that in the limited apertures, the detection probability spectrum of the LOAMM system is inversely proportional to OAM mode numbers, strength of turbulence, and propagation distance. The bit-error rate and aggregate capacities are compared between the traditional OAM-based space-division-multiplexing (OAM-SDM) system with Bessel beams and our proposed LOAMM system. Our work should contribute to proving that the LOAMM system has a number of advantages over the OAM-SDM system in FSO communication.